Cross Sectional study to asses housing conditions and to compare it with education and socio economic status of a semi urban area in Mangalore : A Pilot study - M., Sudharani; Kundapur, Rashmi; Kiran, K. G.; Kiran, N. Udaya (Journal of Health and Allied Sciences NU, 2015)
Introduction: Poverty imposes an oppressive weight on India, especially in the rural areas where almost three out of four Indians and 77 percent of the Indian are under poor living conditions. Although poverty has been reduced during the past four decades, it remains painfully high. Provision of adequate housing and amenities are major challenges for human development, particularly among lowincome urban households in developing countries. Often this shortfall is evident from the proliferation of slums and squatters.Objectives: 1. To assess the housing conditions of the semi urban area (Field practice area of KS Hegde Medical Academy).2. To associate these housing conditions with Education and Socio Economic Status.Methodology: Forty houses included under GRAMA KSHEMA project (Field practice area of K S Hegde Medical Academy) were selected. A pilot study with questionnaire to asses housing condition was done. Subjects were interviewed for their education and socioeconomic status.Results: 100% of Graduates, post graduates and Professionals have excellent housing conditions. Poor housing conditions was seen as the level of education decreased to high school and post high school. Housing conditions were excellent as the socioeconomic class increased. 66.6% of Class I population has excellent housing conditions. 63% of Class II population has good housing conditions and 38.5% of Class IV population has poor housing conditions.Conclusions: It was found that majority of the population had good housing conditions. Education and Socio economic status has an impact on Housing condition.
Keywords: Housing Condition; Education; Socio Economic Status